2015
DOI: 10.1155/2015/939431
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Dexmedetomidine on Stress Hormones, Inflammatory Markers, and Postoperative Analgesia after Functional Endoscopic Sinus Surgery

Abstract: Background. A strong ongoing intraoperative stress response can cause serious adverse reactions and affect the postoperative outcome. This study evaluated the effect of intranasally administered dexmedetomidine (DEX) in combination with local anesthesia (LA) on the relief of stress and the inflammatory response during functional endoscopic sinus surgery (FESS). Methods. Sixty patients undergoing FESS were randomly allocated to receive either intranasal DEX (DEX group) or intranasal saline (Placebo group) 1 h b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 34 publications
(36 reference statements)
1
46
0
1
Order By: Relevance
“…Surgical trauma, a main cause of postoperative pain, leads to peripheral sensitization via the release of inflammatory mediators from immune cells and nonneuronal cells in the periphery. Additionally, a peripheral nociceptive stimulus from surgical trauma directly can cause central sensitization . Dexmedetomidine administration was reported to decrease the level of inflammatory cytokines such as IL‐6 and TNF‐α after nasal surgery group in a previous study.…”
Section: Discussionmentioning
confidence: 91%
“…Surgical trauma, a main cause of postoperative pain, leads to peripheral sensitization via the release of inflammatory mediators from immune cells and nonneuronal cells in the periphery. Additionally, a peripheral nociceptive stimulus from surgical trauma directly can cause central sensitization . Dexmedetomidine administration was reported to decrease the level of inflammatory cytokines such as IL‐6 and TNF‐α after nasal surgery group in a previous study.…”
Section: Discussionmentioning
confidence: 91%
“…No other systematic review or meta‐analysis was found pertaining to perioperative and postoperative analgesic use for endoscopic sinus surgeries. Thirty‐two studies met the inclusion criteria for this project: all of the included studies were randomized, controlled trials (RCTs). Using the Cochrane Bias tool, we judged 4 studies to be at high risk, 21 to be at moderate risk, 6 to be at low risk, and 1 to be at unclear risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Although our review has included several articles demonstrating the viability of outpatient non‐opioid analgesia, a significant portion of analyses focused on immediate postoperative analgesia. Immediate postoperative pain harbors an outsize impact on psychological factors and physiologic stress; when associated anxiety is controlled, this can potentially decrease the need for subsequent opioids. Furthermore, even for non‐opioid analgesics demonstrated to have efficacy in the immediate postoperative setting, these data reinforce which opioid‐avoiding regimens can be adopted, that is, that opioid alternatives are sufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] To limit the surgeon's inadvertent effects in the opioid crisis, conservative postoperative analgesia after ambulatory surgery has been advocated as an area of improvement; however, aggressive immediate postoperative analgesia is thought to reduce subsequent analgesic requirements, alleviate anxiety, and improve patient satisfaction. 9,10 Thus, continued evaluation of prescription patterns as well as exact opioid usage for specific procedures and common surgical combinations is necessary to ensure effective pain management, reduce opioid diversion, and potentially limit opioid dependence. 8 Sinonasal surgical procedures are among the most common operations performed in otolaryngology, with over 260,000 septoplasties and 250,000 of these performed annually.…”
mentioning
confidence: 99%